Constellations d'Empire Territorialisation et construction impériale dans les Amériques hispaniques (xviie-xviiie siècle) - Zuñiga, Jean-Paul (Bibliothèque de la Casa de Velázquez, 2023)
This book looks at the Hispanic monarchy in America through its ability to territorialize the spaces theoretically under its control. While the analysis confirms the central role played by the city, its novelty lies in the effort made to spatialize and contextualize the notions of territorialization and circulation. The Spanish Empire appears as an atomized urban archipelago, favoring the affirmation of original idiosyncratic poles captured through the polysemy of the term "caste", often reduced to the global concept of "race" by historiography. On the contrary, this book demonstrates the importance of specific forms of experience in defining belonging, while highlighting the social construction of spaces revealed by the circulation of the idea of "caste".